Effect of residue and nutrient management on productivity, nutrient uptake, economics and greenhouse gas emission of rice in intensified rice-based cropping systems - Jena, Jagadish; Panda, Bipin Bihari; Pandey, Narendra; Nayak, A K; Nayak, P K (ORYZA-An International Journal of Rice, 2021)
A long-term field experiment was conducted at Institutional research farm, ICAR-National Rice Research Institute, Cuttack, Odisha since 2012-13. The experiment was conducted in a split plot design involving two cropping systems i.e., rice-maize-cowpea (R-M-C) and rice-groundnut-cowpea (R-G-C) covering three crops in three seasons i.e., kharif, rabi and summer, respectively in main plots and five nutrient management treatments i.e., controlÂ control - control (C-C-C), RDFÂ RDF - RDF (R-R-R), Residue Incorporation (RI) +75% of RDFÂ RDF - RDF (RI+R75-R-R), RI+ 75 % of RDF-Straw Mulching (SM) + RDF - RDF (RI+R75-SM+R-R) and RI+75 % of RDF - SM+RDF - 50 % of RDF (RI+R75-SM+R-R50) in sub-plots; where control indicates no fertilizer application to each crop of the system, RDF indicates recommended dose of fertilizers for respective crops, RI indicates cowpea residue incorporation in succeeding rice crop before transplanting and SM indicates rice straw mulching @ 6 t ha-1 in succeeding groundnut and maize.Â Significant improvement in growth parameters of rice i.e., plant height, tillers plant-1, leaf area index, dry matter accumulation, yield i.e., grain yield, straw yield, harvest index, nutrient uptake, economic gain i.e., gross return, net return and B:C ratio, CH4 flux in cowpea residue incorporated treatments than the residue removal treatments. Cowpea residue incorporationÂ with 75% of recommended dose of fertilizer to rice followed by straw mulching with recommended dose of fertilizer to rabi season crops i.e., maize and groundnut and recommended dose of fertilizer to summer season crops i.e., RI+R75-SM+R-R recorded 10.2% higher number of tillers hill-1, 17.1% higher LAI, 10.9% higher DMA, 8.5% higher panicles m-2 and 8.8% higher filled grains panicle-1than recommended dose of fertilization to each crop i.e., R-R-R.RI+R75-SM+R-R also recorded 11.3% higher grain yield, 9.7% higher straw yield, 13.7% higher N uptake, 15.8% higher P uptake, 11.9% higher K uptake, 11.3% higher gross return, 15.1% higher net return and 25.6% less N2O emission than recommended dose of fertilization to each crop i.e., R-R-R. Cowpea residue incorporation with 25% reduction in RDF, straw mulching with RDF to rabi season crops i.e., maize and groundnut and RDF to summer season crops (RI+R75-SM+R-R) however recorded at par growth, yield, nutrient uptake and economic return to that of RI+R75-SM+R-R50. Thus, RI+R75-SM+R-R50 could be useful in achieving higher productivity and profitability from rice in an intensified rice-based cropping system.